Idle Funds of Local Governments and the Quality of Financial Management: A Narrative Literature Review of APBD Absorption Determinants in Indonesia - Desak Nyoman Elita; Gede Adi Yuniarta; Nyoman Ari Surya Dharmawan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The phenomenon of local government idle funds reaching IDR 234 trillion in the third quarter of 2025, coupled with APBD (Regional Budget) expenditure realization of only 65.3% of the approved ceiling as of November 2025, reflects complex structural problems in public financial management in Indonesia. This study aims to conduct a systematic narrative literature review to identify and synthesize the determinant factors affecting APBD absorption. A total of 15 articles obtained from the Emerald, Scopus, ScienceDirect, and Google Scholar databases—spanning publications from 2014 to 2026—were comprehensively reviewed. The analysis is grounded in Agency Theory (Jensen & Meckling, 1976) as the grand theory, complemented by perspectives from Public Choice Theory and Institutional Theory. The review identifies six clusters of determinant factors: (1) weaknesses in internal control systems and financial statement quality; (2) budget transparency and fiscal accountability; (3) quality of performance-based planning and budgeting; (4) procurement processes; (5) the capacity of regional financial apparatus; and (6) limitations of regional financial information systems. The phenomenon is further compounded by high dependence on central transfers, regulatory inconsistencies, and opportunistic behavior stemming from information asymmetry in the principal-agent relationship. These findings imply the need for simultaneous and systemic institutional reform to address the fiscal paradox of Indonesian local governments.